Effect of Jigsaw Type Cooperative Learning Model on Mathematics Learning Results of Grade II Students SDN 20 Situng: Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Matematika Siswa kelas II SDN 20 Situng - zainidar zainidar (Journal of Vocational Education and Information Technology (JVEIT), 2020)
This research aims to determine the effect of the use of jigsaw-type cooperative learning models on students' learning outcomes in Mathematics subjects on multiplication materials and the division of grade II students of SD Negeri 20 Sitiung. This type of research is a quasi expriment of design experiments conducted by giving pre test and post test. The design of this study uses quasi experimental type nonequivalent control group design. The data collection techniques used in this study are tests of belaja results, observations and documentation. Data analysis techniques for student learning results use descriptive analysis, prerequisite tests in the form of normality and homogenity tests and hypothesis tests using t-tests. The average pre-test score of the exprimen class was 64.74, while the control class was 62.50. In addition, the average post-test value of the exprimen class is 73.68 and the control class is 63.61. In the exprimen class, the average study result was 8.94 while in the control class by 1.11. Based on the t test on the difference in the score scoring in the exprimen class and the class control t value of (0.039 < 0.05 ). Based on the results of the above research, it shows that the cooperative learning model of jigsaw type affects students' learning outcomes.